Identification of Nontuberculous Mycobacteria in Patients with Pulmonary Diseases in Gyeongnam, Korea, Using Multiplex PCR and Multigene Sequence-Based Analysis - Min-Jeong Kim; Kyu-Min Kim; Jeong-Ih Shin; Jong-Hun Ha; Dong-Hae Lee; Jeong-Gyu Choi; Jin-Sik Park; Jung-Hyun Byun; Jung-Wan Yoo; Seokyong Eum; Myunghwan Jung; Seung Chul Baik; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Nontuberculous mycobacteria (NTM) are widely present in environments, such as soil and water, and have recently been recognized as important pathogenic bacteria. The incidence of NTM-related infections is steadily increasing. As the diagnosis and treatment of NTM infection should be distinguished from tuberculosis, and the treatment should be specific to the species of NTM acquired, accurate species identification is required. Methods. In this study, two-step multiplex PCR (mPCR) and multigene sequence-based analysis were used to accurately identify NTM species in 320 clinical isolates from Gyeongsang National University Hospital (GNUH). In particular, major mycobacterial strains with a high isolation frequency as well as coinfections with multiple species were diagnosed through two-step mPCR. Multigene sequencing was performed to accurately identify other NTM species not detected by mPCR. Variable regions of the genes 16S rRNA, rpoB, hsp65, and 16S-23S rRNA internal transcribed spacer were included in the analysis. Results. Two-step mPCR identified 234 (73.1%) cases of M. intracellulare, 26 (8.1%) cases of M. avium subsp. avium, and 13 (4.1%) cases of M. avium subsp. hominissuis infection. Additionally, 9 (2.8%) M. fortuitum, 9 (2.8%) M. massiliense, 2 (0.6%) M. abscessus, and 4 (1.2%) M. kansasii isolates were identified. Coinfection was identified in 7 (2.2%) samples. The sixteen samples not classified by two-step mPCR included 6 (1.9%) cases of M. chimaera, 4 (1.3%) M. gordonae, 1 (0.3%) M. colombiense, 1 (0.3%) M. mageritense, and 1 (0.3%) M. persicum identified by sequence analysis. Conclusions. The results of this study suggest a strategy for rapid detection and accurate identification of species using two-step mPCR and multigene sequence-based analysis. To the best of our knowledge, this study is the first to report the identification of NTM species isolated from patients in Gyeongnam/Korea.